ANALISIS PREFERENSI GENERASI MILENIAL DALAM MEMILIH HUNIAN DI KOTA JAMBI - Rethabfahisa, Gustra Tiara; Ariyanto, Edi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study analyzes the housing preferences of the millennial generation in Jambi City. The primary objective is to identify the factors influencing millennials' decision-making in home purchases, including socio-economic demographics, lifestyle, and housing attributes. Data was collected through an online questionnaire using a random sampling method. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM), with total 400 respondent. The results show that socio-economic demographic factors such as income, education level, and employment status significantly influence housing preferences. Additionally, a modern lifestyle emphasizing comfort and accessibility also plays a crucial role. Housing attributes such as location, facilities, and developer reputation were found to be significant factors in purchasing decisions. These findings can be used by housing developers to design properties that meet millennial needs and by policymakers to formulate inclusive and affordable housing policies.